Functionalization-Induced Breathing Control in Metal-Organic Frameworks for Methane Storage with High Deliverable Capacity - Kundu, Tanay (AMERICAN CHEMICAL SOCIETY, 2020)
10.1021/acs.chemmater.8b05332